1991
DOI: 10.1136/gut.32.8.949
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative activity of neuroendocrine tumours of the gastroenteropancreatic endocrine system: DNA flow cytometric and immunohistological investigations.

Abstract: The proliferative activity of 16 tumour specimens from 13 patients with neuroendocrine tumours of the gastroenteropancreatic endocrine system was studied by DNA flow cytometry and immunohistology for the nuclear Ki67 proliferation antigen. Equivalent results were obtained with both methods, which showed the proliferative activity of gastroenteropancreatic neuroendocrine tumours to be heterogeneous. In Since the growth of gastroenteropancreatic neuroendocrine tumours is not yet understood we studied the proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 10 publications
(1 reference statement)
1
10
0
Order By: Relevance
“…The difference between the two groups achieved a P-value of only 0.09, perhaps because of the small sample size and the high cut-off to define Ki-67 positivity. Others have proposed that the Ki-67 proliferation index may assist planning of therapy [56,57]. In particular, a high index may characterize a late clinical phase in a neuroendocrine tumor's history and may justify more aggressive treatment such as chemotherapy targeted to a more malignant tumor phenotype.…”
Section: Histochemical Markersmentioning
confidence: 98%
See 1 more Smart Citation
“…The difference between the two groups achieved a P-value of only 0.09, perhaps because of the small sample size and the high cut-off to define Ki-67 positivity. Others have proposed that the Ki-67 proliferation index may assist planning of therapy [56,57]. In particular, a high index may characterize a late clinical phase in a neuroendocrine tumor's history and may justify more aggressive treatment such as chemotherapy targeted to a more malignant tumor phenotype.…”
Section: Histochemical Markersmentioning
confidence: 98%
“…This index has been proposed in the WHO classification of GI endocrine tumors: (1) well-differentiated endocrine tumor (carcinoid) <2% Ki-67 positive cells, (2) well-differentiated endocrine carcinoma (malignant carcinoid) 2-15% Ki-67 positive cells, and (3) poorly differentiated endocrine carcinoma (small cell carcinoma) >15% Ki-67 positive cells [9]. Numerous studies have supported the validity of the Ki-67 proliferation index as a prognostic indicator for GI carcinoids, correlating with the size of the primary tumor [49,[51][52][53], lymphatic invasion [53], presence of metastases [49,[53][54][55], higher tumor proliferation activity measured by DNA flow cytometry [56], and shorter patient survival [49,57,58]. A dissenting study by Kawahara et al concluded that Ki-67 staining did not correlate with malignant behavior [59].…”
Section: Histochemical Markersmentioning
confidence: 99%
“…Several studies have validated the role of Ki-67 staining in grading NETs of the lung [5,6] and gastrointestinal tract [7][8][9][10]; however, some investigators have questioned the use of Ki-67 as an independent prognostic variable [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, this is time consuming and some histopathologists admit to making eyeball estimates of PI rather than counting a sample of 2000 cells 14. Furthermore, studies demonstrating a relationship between Ki-67 PI and prognosis use different methods to calculate PI; some studies use eyeball methods5 6 while others employ more quantitative methods (eg, calculating the area of positive staining in a fixed area7 or manually counting a sample of cells8 9). Methodological inconsistency in these studies calls into question the applicability of their results to the methods used by histopathologists clinically to calculate PI, and consequently its value as a prognostic indicator in patient management.…”
Section: Introductionmentioning
confidence: 99%